An comparative analysis of different models of belief revision using information from multiple sources - Tamargo, Luciano H. (2008)
In this work we analyze the problem of knowledge representation in a collaborative multi-agent system where agents can obtain new information from others through communication. Namely, we analyze several approaches of belief revision in multi-agent systems. We will describe different research lines in this topic and we will focus on Belief Revision using Information from Multiple Sources. For this, we are going to accomplish a comparative analysis of different models of belief revision that use information from multiple sources.